Improving efficacy of TNBC immunotherapy: based on analysis and subtyping of immune microenvironment - Yang, Yalan; Li, Haifeng; Yang, Wei; Shi, Yanxia (Frontiers in Immunology, 2024)
Triple-negative breast cancer (TNBC) is a highly aggressive type of breast cancer that encompasses several distinct subtypesRecent advances in immunotherapy offer a promising future for the treatment of these highly heterogeneous and readily metastatic tumors. Despite advancements, the efficacy of immunotherapy remains limited as shown by unimproved efficacy of PD-L1 biomarker and limited patient benefit. To enhance the effectiveness of TNBC immunotherapy, we conducted investigation on the microenvironment, and corresponding therapeutic interventions of TNBC and recommended further investigation into the identification of additional biomarkers that can facilitate the subtyping of TNBC for more targeted therapeutic approaches.Triple-negative breast cancer (TNBC) is a highly aggressive subtype with dismal long-term survival due to the lack of opportunities for traditional endocrine and targeted therapies. Recent advances in immunotherapy have shown promise, but response rates can be limited due to the heterogeneous tumor microenvironments and developed therapy resistance, especially in metastatic cases. In this review, we will investigate the tumor microenvironment of TNBC and corresponding therapeutic interventions. We will summarize current subtyping strategies and available biomarkers for TNBC immunotherapy, with a particular emphasis on the need for further research to identify additional prognostic markers and refine tailored therapies for specific TNBC subtypes. These efforts aim to improve treatment sensitivity and ultimately enhance survival outcomes for advanced-stage TNBC patients. Immunotherapy (IM) emerges as a promising therapeutic strategy for TNBC by leveraging immune system to identify and eradicate tumor cells. Several clinical trials have demonstrated the potential benefits of IM for TNBC patients, especially when combined with chemotherapy (Ignatiadis et al.